Ratting : the use and abuse of informants in the American justice system - Bloom, Robert M., 1946- (Praeger, 2002)
The use of police informants in the criminal justice system presents a range of potential pitfalls. Bloom illuminates the pernicious legal ramifications that can result from the justice system's relationship to and use of informers providing insights into law enforcement techniques as well as the Court's response to them. Law professors, criminologists, and law enforcement scholars will find Bloom's account of this much used and abused but under-reported aspect of America's law enforcement efforts both edifying and sobering.